2006
DOI: 10.1002/sce.20148
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the earth systems of Malawi: Ecological sustainability, culture, and place‐based education

Abstract: ABSTRACT:The purpose of this 2-year study was to investigate Malawian teacher educators' perspectives and dispositions toward teaching about ecological sustainability issues in Malawi, a developing country in sub-Sahara Africa. This study was embedded in a larger theoretical framework of investigating earth systems science through the understanding of nature-knowledge-culture systems from local, place-based perspectives. Specifically, we were interested in learning more about eco-justice issues that are relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…In a response to Barnhardt et al (2008) demonstrate that these spaces of possibility already exist in the science communities where science-pluralism is valued. International scholars have also written about the contributions of aboriginal peoples in Malawi (e.g., Glasson et al 2006). We are reminded that science and science education cannot exist in a vacuum.…”
Section: Paying Selective Attentionmentioning
confidence: 98%
“…In a response to Barnhardt et al (2008) demonstrate that these spaces of possibility already exist in the science communities where science-pluralism is valued. International scholars have also written about the contributions of aboriginal peoples in Malawi (e.g., Glasson et al 2006). We are reminded that science and science education cannot exist in a vacuum.…”
Section: Paying Selective Attentionmentioning
confidence: 98%
“…As discussed later, this problem is very similar to our research on ecological sustainability, culture, and education in Africa (e.g. Glasson et al 2006); we (Western researchers) were the ''they'' that is part of the dominant Eurocentric culture.…”
mentioning
confidence: 86%
“…During our initial work in Malawi (Glasson et al 2006), we learned first hand from Malawian educators in a science methods class about the issues associated with tea plantations, including land that was acquired from the chiefs for nominal gifts and how the profits go to European landowners. Although the land surrounding the tea plantations is ''shared'' with local villagers on the outskirts of the plantations, the Malawians lack legal ownership or access to irrigation in vast acres of the most fertile land in the country.…”
Section: Connections To Research On Efs In Malawi Africamentioning
confidence: 99%
“…However, the sustainability education literature, though still small, shows growing awareness of the urgency for educators to make changes in the ways they educate and in the content of their courses and curricula (Huisingh, 2006). Recent publications examine place-based (Glasson et al, 2006) and backcasting (Quist et al, 2006) approaches to teaching sustainability in engineering. Riley et al (2006) demonstrated that engaged approaches in architecture and engineering courses contribute to a heightened awareness among students of the importance of sustainability.…”
Section: New Developments In Sustainability Educationmentioning
confidence: 99%